Justification Of Input Parameters For Non-Contact Sensors In Automatic Cotton Harvesting Machine Systems - Abdazimov A.D., Omonov N.N. (International Journal of Advanced Science and Technology, 2020)
By the analysis of the state of automation of vertical spindle cotton harvesters it is established the reasons of insufficient reliability and efficiency of automation systems - the use of mechanical contact sensors, contacting with the objects of receiving the input signal (bed surface, rows and sizes of cotton stems, etc.) and substantiated the expediency of using contactless digital optical primary converters. Methodology and results of field research on selection of input parameters from external characteristics of cotton bushes and boxes for advanced systems of automatic control and management of technological parameters of cotton harvester with non-contact sensors are covered. Correlation interrelationships of characteristics of bushes and boxes of the basic regionalized grades of cotton are investigated, by their results input parameters which can be apprehended by developed contactless primary converters of systems of automatic driving of the cotton-harvesting machine, regulation of height of an arrangement and width of a working slot of the harvesting device, and also the control of losses of a crop behind the harvesting device are recommended.